Cardiac donors with renal impairment: Usage and outcomes after heart transplant. Issue 9 (14th July 2022) - Jaiswal, Abhishek; Baran, David A; Sinphurmsukskul, Supanee; Baker, William L
Abstract: Introduction: Utilization of hearts from donors with significant renal dysfunction and the impact of donor renal function on outcomes following heart transplant (HT) is unknown. We sought to investigate the trends, characteristics and outcomes associated with these donor hearts and the impact of donor renal function on survival and graft failure in adult HT recipients. Methods: We reviewed the Scientific Registry of Transplant Recipients (SRTR) and summarized trends, characteristics and outcomes of hearts from adult donors by renal impairment. Single‐organ HTs were evaluated and stratified by donors with estimated glomerular filtration rate (eGFRs) < and ≥30 ml/min. We constructed Cox proportional hazards regression models to compare time‐to‐mortality over 30‐day, 1‐, 3‐, and 5‐year time‐horizons between groups, and the association of donor eGFR group with graft failure. Results: A total of 162, 586 adults were evaluated for cardiac donation, of which, 22, 780 (14%) had an eGFR ≤ 30 ml/min. Donors with an eGFR ≤ 30 ml/min increased over time, from 7.2% (358/4966) in 2000 to a high of 19.5% (2283/11, 728) in 2020. Such donors were significantly more likely discarded (not offered (7.9% vs. 9.8%, p  < .001) or accepted (62.6% vs. 72.2%, p  < .001), and less likely to be transplanted (18.0 % vs. 29.5%; p  < .001). Of 41, 044 HT recipients, 3906 (9.5%) had hearts from such donors. Primary graft failure was similar between groups (OR 1.20, 95% CI .91–1.58; p  = .1) while adjusted mortality was lower for recipients from donors with eGFR ≤ 30 ml/min. Conclusions: More than two‐third of hearts from donors with renal dysfunction are discarded. Recipients from donors with renal dysfunction sustained lower mortality post HT during the study period. Increased evaluation and utilization of donors with renal dysfunction has the potential to expand the critically low donor pool.